Influencia del ambiente familiar en el rendimiento educativo de los estudiantes de bachillerato de la unidad educativa Dr. Juan Henríquez Coello de la ciudad de Machala provincia de El oro periodo lectivo 2014 - 2015. - Uchuari Flores, Ruth Elizabeth (2015)
This research is based on the fundamental role of parents in conducting extracurricular tasks of their children, as well as the limited time spent in the company and supervision, due to the long hours of work, which prevents or hinders the parent, has longer living with their children. Detected a problem occurred in the society of the influence of parents on the academic performance of their children.